Low-frequency vibrations of DNA and base pair opening - Merzel, Franci (Acta chimica slovenica, 2011)
DNA melts at temperatures around 70 °C (~340 K) depending on the base-pair composition, level of hydration, type of counterions and excess salt concentration. Vibrational modes, which increase the separation between base molecules, i.e. perform the base pair opening, are thought to play an important role in DNA-bubble formation but these are typically assigned frequencies around 90 cm-1 (120 K). Understanding DNA melting and related biological processes requires this apparent energy gap of more than 200 K to be understood. We have performed atomistic molecular simulations which enable us to reconcile this energy difference between cause and effect. Using quasi-harmonic analysis we have analyzed the way in which vibrational modes of DNA change with the temperature.
Keywords: base-pair opening; B-DNA; DNK; kemijska struktura; kvaziharmonska analiza; molecular dynamics simulations; quasiharmonic analysis; tališče; vibrational density of states